2021
DOI: 10.46557/001c.24843
|View full text |Cite
|
Sign up to set email alerts
|

Geopolitical Risk and the Return Volatility of Islamic Stocks in Indonesia and Malaysia: A GARCH-MIDAS Approach

Abstract: In this paper, the predictive value of geopolitical risk (GPR) for the return volatility of Islamic stocks in Indonesia and Malaysia is examined. GPR data, whether global or country-specific, heighten the return volatility of Islamic stocks in both countries, albeit with a greater impact on Indonesia. Additional analyses show improved out-of-sample forecast gains with the inclusion of GPR data in the predictive model of the return volatility of Islamic stocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…(2019), Abbas et al . (2022) and Ndako et al . (2021) concluded that Islamic securities including stock and SUKUK are more resilient to the geopolitical shocks as compared to its conventional counterparts and can serve as a safe haven for the investors during the financial crises.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…(2019), Abbas et al . (2022) and Ndako et al . (2021) concluded that Islamic securities including stock and SUKUK are more resilient to the geopolitical shocks as compared to its conventional counterparts and can serve as a safe haven for the investors during the financial crises.…”
Section: Introductionmentioning
confidence: 95%
“…Choi, 2021;Heller and Phillips, 2020;JEBABLI et al, 2022;Mensi et al, 2022;Pence, 2022;Rizvi and Itani, 2022;Yousaf et al, 2022;Sraieb et al, 2022). Several recent studies including Bouri et al (2019), Abbas et al (2022 and Ndako et al (2021) concluded that Islamic securities including stock and SUKUK are more resilient to the geopolitical shocks as compared to its conventional counterparts and can serve as a safe haven for the investors during the financial crises. In an another study, Tiwari et al (2020) concluded that gold can serve as a safe hedge against the oil returns in the short and medium run, but in the Impact of geopolitical risk long run, it cannot protect the investors against the increasing oil prices due to the GPRs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Fang et al (2018) adopt GARCH-MIDAS model to examine the predictability of global economic policy uncertainty (GEPU) for gold market behaviour, and their results suggest a strong forecasting power of GEPU for future monthly volatilities for the aggregate global gold futures market (out-of-sample tests inclusive). In particular, probing the predictive content of GPR for Islamic stock return volatility with special interest in Indonesia and Malaysia, Ndako et al (2021) conclude that GPR heighten the return volatility in these countries. In other words, Islamic stock return volatility is vulnerable to GPR in the two countries.…”
Section: Introductionmentioning
confidence: 97%
“…Sequel to our attraction to GARCH-MIDAS, studies such as Wang (2010), Girardin andJoyeux (2013), Fang, Chen, Honghai andQian (2018), Wang et al (2020), Ndako, Salisu andOgunsiji (2021) among others, have adopted the same method for the same reason espoused in this paper. Consequently, a GARCH approach is used by Wang (2010) to show that the volatility of inflation causes stock market volatility in China.…”
Section: Introductionmentioning
confidence: 98%
“…The use of Garch-Midas model has become rather popular in economic literature, researchers using it to analyse different relationships (see, Girardin and Joyeux, 2013, Fang et al, 2018, Salisu et al, 2020Wang et al, 2020, Ndako et al, 2021Salisu and Gupta, 2021;Salisu et al, 2022a;Salsiu et al, 2022b, andSalisu et al, 2023 among others). For instance, employed this approach to explain the connection between geopolitical risk (GPR) and stock market volatility in emerging economies.…”
Section: Introductionmentioning
confidence: 99%